The Correlation between Leprosy Types and Reactions with Disability of Leprosy Patients in Universitas Mataram Hospital - Wayan Julita Krisnanti Putri; Yunita Hapsari; Dinie Ramdhani Kusuma (Jurnal Ners, 2023)
The purpose of this study is to analyze the correlation between leprosy types and reactions with the disability occurrence of leprosy patients in the outpatient clinic of Universitas Mataram (UNRAM) Hospital.  This study was an analytical observational study with a retrospective approach and cross-sectional design. Medical records of leprosy patients were utilized to gather the information from January 2021-April 2023. The Fisher-exact test was used to analyze the data.  There were 25 patients included in the study. There were 15 male patients (60%) while women were 10 patients (40%). In the majority, there were 12 patients (48%) around 25-45 years old. Based on occupation, fourteen patients (56%) were unemployed followed by 9 employed patients (36%). Furthermore, there were 24 patients (96%) who suffered from multibacillary leprosy. Twenty patients (80%) had type 1 reactions while the other 5 patients (20%) had type 2 reactions. Among leprosy patients, there were 17 disabled patients due to leprosy in this study. There was no association between leprosy types and disability occurrence (p-value 1.0). The correlation between leprosy reactions and disability was not significant either in UNRAM Hospital (p-value 0.28). There was no association between leprosy types and reactions to disability of leprosy patients in UNRAM Hospital.